Is gastroesophageal reflux contribute to the development chronic cough by triggering pulmonary fibrosis - Aksu, Oğuzhan; Songür, Necla; Songür, Yıldıran; Öztürk, Önder; Adiloğlu, Ali Kudret; Kapucuoğlu, Nilgün; Akın, Mete (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Previous studies have shown that the prevalence of abnormal acid reflux in fibrotic lung disease patients is high, and in particular, patients with secondary pulmonary fibrosis show higher esophageal acid exposure than normal controls. There are also some findings that, in patients with pathological reflux, pulmonary fibrosis may develop. The aim of this study is to investigate if pulmonary fibrosis is involved in the pathogenesis of chronic cough due to Gastroesophageal Reflux. Materials and Methods: A prospective study was performed in twenty-one patients with chronic cough due to gastroesophageal reflux who was diagnosed as reflux esophagitis by upper gastrointestinal endoscopy, histology, and in ten healthy controls without GER or any lung disease. All participitants underwent laryngoscopic examination and gastroesophageal scintigraphy with late lung imaging. Bronchoalveolar lavage fluid total and differential cell counts, T and B cell subsets, and the concentrations of IL- 1β and TNF-α were measured. Results: Reflux extending into the proximal esophagus was noted in 52.5%, and posterior laryngitis was present in 90.5% of the patients. No evidence of pulmonary aspiration was noted in the patients with reflux on scintigraphic examination. No significant difference was found between the GER and control groups in terms of cellular content, IL-1β and TNF-α levels or mean T cell subsets and B cell counts in bronchoalveolar lavage fluid. Forced expiratory volume in one second, forced vital capacity FEV1/FVC, total lung capacity, and carbon monoxide diffusion capacity values were within normal limits in the gastroesophageal reflux group. Conclusion: Our findings do not support the hypothesis that gastroesophageal reflux leads to chronic cough by triggering alveolar epithelial injury and subsequent pulmonary fibrosis.